The crisis of global capitalism : Pope Benedict XVI's social encyclical and the future of political economy - Pabst, Adrian (James Clarke and Co., 2012)
The current economic crisis stems from a deeper crisis of cultural imagination and civilisational ethics: here is the starting point of this collection of essays which draw a new political economy facing the crisis of Western civilization. This book gathers together a range of audacious and provocative readings of Caritas in Veritate, the first papal encyclical that addresses issues immediately relevant for politic, economic, and social theory. These readings embody the kind of fruitful dialogue Pope Benedict XVI wanted to generate with his radical discourse for an alternative political econom.